THE ROLE OF BLOCKCHAIN TECHNOLOGY IN FACING REVOLUTION EDUCATION 4.0 - Agung Rizky; Shatya Silen; Desandio Ananda Putra (BEST Journal (Biology Education, Sains and Technology), 2021)
Although several concepts for implementing education exaggerated using blockchain technology, t agreements which are allocated ledgers carefully and thoroughly. Blockchain technology, unlike databases that are processed by certain forces that provide policies in correctness of data through real-time implementation, Blockchain is a digital data storage system containing records that are connected via cryptography. Blockchain technology has now been used by various sectors, one of which is for transactions in cryptocurrencies such as Bitcoin. The benefit of the blockchain technology approach in education is that people who do not have knowledge of blockchain technology can benefit from blockchain technology, because a lot of the data generated by this sector is continuous from education to Bachelor. Blockchain, can be used as, "a machine to create high-level security and reliable security", the high level of security and efficiency of blockchain as a storage place for financial transactions and data has opened up opportunities for innovation in education as a storage for educators and students' data.